Political and Society Communication of the Korean Drama “Queen Maker” - พลับนิล, น้ำผึ้ง; วัฒนเมธา, วิทยา; จรูญโรจน์, ปริญญา; ใจประดับ, อารีรัตน์; เกงขุนทด, บุญยวีร์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This study, titled Political and Social Communication in the Korean Series Queen Maker, aims to analyze the meaning-making and interpretation of the Korean drama Queen Maker from political and social perspectives. The research applies concepts of narrative structure, semiotics, and political communication as theoretical frameworks to explore how the series functions as a contemporary media text. It highlights struggles for political power, the role of women in society, and competition within the capitalist system, conveyed through complex storytelling and diverse symbolic representations. The series was selected through purposive sampling, as it has gained international popularity and distinctly presents political and social themes.The findings offer an understanding of the narrative structure in relation to socio-political dimensions, the decoding of embedded semiotic elements, and the mechanisms of political communication in contemporary entertainment media. This contributes to a broader comprehension of how such series influence viewers' thoughts, attitudes, and perceptions within modern society. Additionally, the study reflects the role of the South Korean media industry as a powerful tool in reproducing or critiquing social and political ideologies through implicit communication.